2016
DOI: 10.1002/bjs.10148
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of outcomes after distal pancreatectomy with coeliac axis resection for locally advanced pancreatic cancer

Abstract: Distal pancreatectomy with coeliac axis resection seems a valuable option for selected patients with pancreatic cancer involving the coeliac axis with acceptable morbidity and mortality, and a median survival of 18 months when combined with (neo)adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 42 publications
6
42
1
Order By: Relevance
“…With a comparable median survival of 18 months, especially adjuvant therapy was found to be a significant prognostic factor in the DP‐CAR collective. A recent systematic review on 19 studies included 240 patients and confirmed that, despite a considerable morbidity, this procedure can be performed with a low mortality of 3.5% and results in 15 months median survival, which increases to 18 months if resection is embedded in a multimodal therapy approach …”
Section: Neoadjuvant Therapy In Borderline Resectable Pancreatic Cancermentioning
confidence: 98%
“…With a comparable median survival of 18 months, especially adjuvant therapy was found to be a significant prognostic factor in the DP‐CAR collective. A recent systematic review on 19 studies included 240 patients and confirmed that, despite a considerable morbidity, this procedure can be performed with a low mortality of 3.5% and results in 15 months median survival, which increases to 18 months if resection is embedded in a multimodal therapy approach …”
Section: Neoadjuvant Therapy In Borderline Resectable Pancreatic Cancermentioning
confidence: 98%
“…The frequency with which patients respond or remain with stable disease that can lead to resection is encouraging, but needs to be enhanced . A recent systematic review has confirmed the role of surgical therapy in which 19 studies involving 240 patients were included, which demonstrated a 18 (10‐26) month overall survival in the patients that were treated with neo‐adjuvant therapy …”
Section: Role Of Surgery—resection and Electroporationmentioning
confidence: 99%
“…[44][45] A recent systematic review has confirmed the role of surgical therapy in which 19 studies involving 240 patients were included, which demonstrated a 18 (10-26) month overall survival in the patients that were treated with neo-adjuvant therapy. 46…”
Section: Role Of Surgery-resection and Electroporationmentioning
confidence: 99%
“…However, some surgical centers reported good outcomes after arterial resections (55), particularly for distal pancreatectomies with celiac axis resection (56,57).…”
Section: Borderline Resectable Pdacmentioning
confidence: 99%